Prognostic Value of Maternal Cardiovascular Hemodynamics in Women With Gestational Hypertension and Chronic Hypertension in Pregnancy. Issue 2 (August 2020) - Kalafat, Erkan; Perry, Helen; Bowe, Sophie; Thilaganathan, Basky; Khalil, Asma
Abstract : This study aimed to assess the prognostic value of cardiovascular assessment in women with gestational hypertension or chronic hypertension for the risk of preeclampsia and need for closer antenatal surveillance. This was a prospective study of pregnancies complicated by gestational hypertension or chronic hypertension presenting to St George's Hospital, between January 2015 and May 2018. A noninvasive ultrasonic cardiac output monitor was used to obtain cardiovascular variables of cardiac output (CO) and systemic vascular resistance (SVR) and weight-adjusted indices. The primary outcome was the time to development of preeclampsia in women with gestational hypertension or chronic hypertension. In women with gestational hypertension or chronic hypertension (n=149), cox-proportional hazards analysis showed that mean arterial pressure ( P =0.006), Afro-Caribbean ethnicity ( P =0.045), and gestational age at the time of diagnosis above 34 weeks ( P <0.001) were significantly associated with increased risk of earlier preeclampsia. Women with high SVR and normal CO (adjusted hazard ratio, 2.32 [95% CI, 1.06–5.08]; P =0.035) and high SVR and low CO (adjusted hazard ratio, 7.79 [95% CI, 1.94–31.24]; P =0.003) cardiovascular profiles had significantly higher risk of earlier preeclampsia compared with women with normal SVR and normal CO. The findings of this study demonstrate that hypertensive women with increased SVR and low CO had a higher risk of developing preeclampsia sooner. Abstract : Supplemental Digital Content is available in the text.